A note on stability and control of sampled-data asynchronous switched systems - Sen, Busra; Turker, Turker; Eren, Yavuz (ELSEVIER, 2022)
High-performance control of switched systems is needed in various applications involving sampled state variables and discrete control signals. However, asynchronous switching phenomenon existing in sampled-data switched systems may introduce undesired response characteristics and even instability. After demonstrating such unfavorable effects, the conditions to check the stability in these systems are provided in this study. Then the control design problem is considered, and an optimal controller design procedure for assorted performance measures is presented for a class of sampled-data switched systems. The performance of the controller is validated through numerical simulations. The proposed control structure is viable in many different applications containing switching phenomena with a discrete control structure.(c) 2021 European Control Association. Published by Elsevier Ltd. All rights reserved.
Keywords: Sampled-data systems; Switched systems; Stability; Optimal control; LYAPUNOV FUNCTION; LINEAR-SYSTEMS; STABILIZATION; Automation & Control Systems